Natural Bioactive Products as Epigenetic Modulators for Treating Neurodegenerative Disorders - Olaia Martínez-Iglesias; Vinogran Naidoo; Iván Carrera; Lola Corzo; Ramón Cacabelos (MDPI AG, 2023)
Neurodegenerative disorders (NDDs) are major health issues in Western countries. Despite significant efforts, no effective therapeutics for NDDs exist. Several drugs that target epigenetic mechanisms (epidrugs) have been recently developed for the treatment of NDDs, and several of these are currently being tested in clinical trials. Furthermore, various bioproducts have shown important biological effects for the potential prevention and treatment of these disorders. Here, we review the use of natural products as epidrugs to treat NDDs in order to explore the epigenetic effects and benefits of functional foods and natural bioproducts on neurodegeneration.